Membrane proteome of the thermoalkaliphile Caldalkalibacillus thermarum TA2.A1 - de Jong, Samuel I.; Sorokin, Dimitry Y.; van Loosdrecht, Mark C. M.; Pabst, Martin; McMillan, Duncan G. G. (Frontiers in Microbiology, 2023)
Proteomics has greatly advanced the understanding of the cellular biochemistry of microorganisms. The thermoalkaliphile Caldalkalibacillus thermarum TA2.A1 is an organism of interest for studies into how alkaliphiles adapt to their extreme lifestyles, as it can grow from pH 7.5 to pH 11. Within most classes of microbes, the membrane-bound electron transport chain (ETC) enables a great degree of adaptability and is a key part of metabolic adaptation. Knowing what membrane proteins are generally expressed is crucial as a benchmark for further studies. Unfortunately, membrane proteins are the category of proteins hardest to detect using conventional cellular proteomics protocols. In part, this is due to the hydrophobicity of membrane proteins as well as their general lower absolute abundance, which hinders detection. Here, we performed a combination of whole cell lysate proteomics and proteomics of membrane extracts solubilised with either SDS or FOS-choline-12 at various temperatures. The combined methods led to the detection of 158 membrane proteins containing at least a single transmembrane helix (TMH). Within this data set we revealed a full oxidative phosphorylation pathway as well as an alternative NADH dehydrogenase type II (Ndh-2) and a microaerophilic cytochrome oxidase ba3. We also observed C. thermarum TA2.A1 expressing transporters for ectoine and glycine betaine, compounds that are known osmolytes that may assist in maintaining a near neutral internal pH when the external pH is highly alkaline.